A Feasibility Study on the Table Top Breast Milk Pasteurizer - Ricafrente, Joanne L.; Romero, Maricelle C.; Villegas, Camilla Natasha B. (Diliman, Quezon City College of Engineering, 2000)
(1) Market Analysis. The Table Top Breast Milk Pasteurizer (Pasteurizer II) is the latest invention developed by the Advanced Science and Technology Institute (ASTI), in cooperation with the Philippine Children?s Medical Center (PCMC), and the Alay Gatas Foundation. The device, which has a capacity of 88 ounces, is used to pasteurize breast milk at a temperature of 62.5 C for twenty five minutes. At this temperature and duration, disease-carrying microorganisms are killed, while antibodies are kept active. The target market for the Pasteurizer II are the Primary, Secondary, and Tertiary hospitals nationwide, both government and private. The supply analysis reveals that there is no supply of pasteurizer in all levels of the hospitals. Though there may be supply sources abroad, they have not yet penetrated the local market. Thus, there is a sufficiently large gap between the demand for and the supply of the Pasteurizer. For the primary hospitals, the demand varies from 375 to 380 units; for the secondary hospitals, the demand ifs from 575 to 585 units, while for the tertiary hospitals, the demand varies from 210 to 215 units. The portion of the gap to be captured is the fraction of the total number of hospitals which are in need for the product and are willing to acquire a unit. For year 1, the market share is 0%, 6.05% and 12.81% for primary, secondary and tertiary hospitals, respectively. At the end of the study period, the market share increases to 33.11% for the primary level, 91.83% for the secondary level, and 94.63% for the tertiary level. From the data gathered and the market opportunity analysis conducted, it can be concluded that there is substantial market for the product. The Pasteurizer II proves to be a promising product, especially since it is the first in the country. Though it has yet to create its own market, its projected total sales are sufficient enough to support the venture. (2) Technical Analysis. The production process of the Pasteurizer II is divided into three main parts: 2.1) the production of the printed circuit board; 2.2) the manufacture of the Pasteurizer vessel; and 2.3) the final assembly. Various technological alternatives are available for mass-producing the Pasteurizer II. The make-or-buy analysis reveals that it would be cheaper to buy the main vessel and the printed circuit board instead of producing them. The main vessel can be bought from Pacific Kitchen, which is a subcontractor that made the vessel for the prototype. It is proposed that the printed circuit board be bought from EPIC Electronics International because of the relatively low cost and their product?s export quality. Since the vessel and the printed circuit board will be out-sourced, the company will only be involved with the final assembly of the product. From the supplier evaluation, it shows that the materials, and the tools/equipment needed for the final assembly should be bought from Alexan Commercial and from General Hardware, respectively. The company will implement a five-day working week. Each working day will have a single shift of 8 hours, with two 15-minute breaks. The company will be employing one general manager, one engineer, one bookkeeper/secretary, one technician, and one utility personnel for the five-year period. One electrician will be employed for the first two years, two electricians for the years 3 and 4, and three electricians for year 5. A facility layout has been designed to satisfy the space requirements of the assembly and office areas. The said facility, which has a total floor area of 70 square meters, will be located on the second floor of the Golden Sun Building in Mindanao Avenue, Quezon City. The total cost necessary to implement the project is Php 2,792,917.37. it consists of fixed investments, venture initiation costs, and a one-year working capital. A 10% contingency allowance is also included in the total project cost. Given the technological alternatives available, and from the analysis done, the production of the Pasteurizer II promises to be a technically feasible project. (3) Financial Analysis. The venture requires a total project cost of Php 2,792,917.37 of this amount; Php 1,400,000.00 will be borrowed from the Technology Applications and Promotion Institute (TAPI), which is an organization which helps fund the projects that are supported by the Department of Science and Technology (DOST). The interest rate for the loan is 13.5%, with five years to pay and one year grace period. The remaining balance, Php1,392,917.37, will be shouldered by the owner of the company, which is the Alay Gatas Foundation. The financial statements (income statement, cash flow statement and balance sheet), which were presented for the five-year study period, shows a positive and increasing trend in the company?s net income and cash flow projections throughout the five-year operating period. Moreover, the financial ratios reveal a stable financial position for the company. Also, the computed net present value (NPV = Php 5,721,349.04) and internal rate of (IRR = 139.82% > MARR = 35%) prove that the project is an acceptable venture. Thus, it is wise to invest in the project. The payback period is 2.0305 years. This suggests that the investment is recovered early in the company?s life. After the evaluation of the results of the financial projections and tests of profitability, the project is deemed to operate profitably, withstand adversities, and raise sufficient cash. As a result, it has the ability to service its debts and generate returns on the investment of financiers. Thus, the project is considered financially feasible. (4) Organization. In establishing the organization of the production of Pasteurizer II, the corporation was selected as the best type of ownership based on the following criteria: business life stability, organizational formalities, and liabilities to owners, taxation, capital infusion and flexibility management. Because the project is owned by Alay Gatas Foundation, a non-stock corporation shall be formed. The organization consists of the members of the corporation, the Board of trustees, the general manager, engineer, secretary, electrician, technician and utility personnel. The organizational structure is arranged in line and staff configuration to define the hierarchy and positions. All employees are subject to SSS, Medicare, employer?s compensation and SSS benefits. The organizational requirements to start the company are feasible. (5) Social Profitability Analysis. The cost-benefit analysis shows that aside from the benefits it gives to the company and to the end-users, the project also has a significant impact in the community. This includes the generation of jobs, the patronization of local materials and suppliers, and the implementation of pasteurization in hospitals nationwide. In addition to these, the municipal tax, corporate income tax, and personal income tax which result from the project will also help both the local government and the national government. These taxes will be used to fund the projects for the country. Furthermore, qualitative benefits, like the motivation of other inventors and innovators, have also been identified, while no other significant disbenefits, besides waste generation, can be attributed to the venture. The net present value (NPV = P 5,721,349.04) and the internal rate of return (IRR = 139.82%) have very attractive values. These values indicate the project?s acceptability and growth potential. Furthermore, a benefit-cost ratio of 1.033 tells us that the benefits outweigh the costs. From the determination of the project?s socio-economic contributions, from the evaluation of the benefits and costs, it can be concluded that the project is socially profitable.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Advance Science and Technology Institute (ASTI); Breast milk--Collection and preservation; Milk--Pasteurization.; Participatory monitoring and evaluation (Project management)